Development of a remote implementation support strategy to enhance integration of depression treatment into primary care settings in rural India - Pedersen, Gloria A.; Haney, Juliana Restivo; Singh, Abhishek; Choubey, Shivangi; Bondre, Ameya; Vorapanya, Vorapat; Bhan, Anant; Tugnawat, Deepak; Patel, Vikram; Naslund, John A.; Ramaswamy, Rohit (Frontiers in Public Health, 2024)
IntroductionContextually responsive implementation support strategies are needed to enhance the integration of mental health services into primary health care. Technical assistance is widely used as a core “capacity building” strategy, primarily for increasing the motivation and capacity of individuals (e.g., frontline workers) to adopt evidence-based interventions in healthcare settings. This article documents the systematic design of a technical assistance strategy for supporting primary care staff (e.g., nurses) in integrating depression care, from screening to treatment, aligned with a non-communicable disease program across seven health facilities in the Sehore District of Madhya Pradesh, India.MethodsWe conducted a mapping exercise of local health facilities with dedicated staff and a literature review to inform the development of the technical assistance strategy.ResultsReporting guidelines guided the structure of the strategy protocol. The evidence-supported strategy, called Remote Coaching Support, is tailored to the local setting. It uses quality improvement methods like the Plan-Do-Act-Study cycle and training materials to help coaches deliver support remotely via video/phone-based calls and WhatsApp messaging with the overall goal of increasing uptake and fidelity of depression screening and referral among primary care staff in alignment with an existing non-communicable diseases program.ConclusionThe development of Remote Coaching Support involved iterative improvements through team meetings and practice-training feedback, though limitations exist due to a lack of systematic implementation standards, especially in this setting. This strategy will be tested in increasing scales to refine its application, with effectiveness and acceptability results to be evaluated in a randomized control trial.